2017
DOI: 10.1038/srep44601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proteomic profiles in the zebrafish retina during experimental degeneration and regeneration

Abstract: Zebrafish spontaneously regenerate the retina after injury. Although the gene expression profile has been extensively studied in this species during regeneration, this does not reflect protein function. To further understand the regenerative process in the zebrafish, we compared the proteomic profile of the retina during injury and upon regeneration. Using two-dimensional difference gel electrophoresis (2D-DIGE) and label-free quantitative proteomics (quadrupole time of flight LC-MS/MS), we analysed the retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Moreover, astrocyte-derived Gal1 has been proposed to play a role in neuromodulation and microglia polarization in a model of multiple sclerosis [24] and in axonal degeneration in a model of amyotrophic lateral sclerosis [62]. Recently, it has been observed that Gal1 is upregulated 2-fold in zebrafish retina during experimental degeneration [63], suggesting that it could play an important role in the repair of the zebrafish retina by providing a permissible environment for regeneration. However, since neural retina displays substantial differences with other nervous system circuits, further studies are needed to dissect the role of Gal1 in retinal neurodegeneration in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, astrocyte-derived Gal1 has been proposed to play a role in neuromodulation and microglia polarization in a model of multiple sclerosis [24] and in axonal degeneration in a model of amyotrophic lateral sclerosis [62]. Recently, it has been observed that Gal1 is upregulated 2-fold in zebrafish retina during experimental degeneration [63], suggesting that it could play an important role in the repair of the zebrafish retina by providing a permissible environment for regeneration. However, since neural retina displays substantial differences with other nervous system circuits, further studies are needed to dissect the role of Gal1 in retinal neurodegeneration in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Histone H2B is one subunit of the histone H2A-H2B heterodimer [81], a key histone component [82]. Histone H2B is up-regulated in zebrafish retina undergoing regeneration [83]. These proteins are highlighted as markers of the retina, which clearly demonstrate the retinal expansion observed by H&E staining.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeleton and membrane transport proteins were altered during regeneration, with the highest fold-change upregulation observed for β-2 tubulin A, histone H2B and brain type fatty acid binding protein. In addition, via gene ontology analysis, reduced metabolic processing and increased fibrin clot formation during degeneration were observed when compared to that in the normal retina (Eastlake et al, 2017). However, further investigations of the energy metabolism of immune cells during zebrafish regeneration are needed.…”
Section: Metabolism and Regenerationmentioning
confidence: 99%